1998
DOI: 10.1038/sj.bmt.1701170
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow transplantation in Shwachman–Diamond syndrome: report of two cases and review of the literature

Abstract: Summary:Patients with Shwachman-Diamond syndrome (SDS) have an increased frequency of myelodysplasia and leukemic transformation. We described two patients who received allogeneic stem cell transplantation and developed multiple complications, including seizure, hyperglycemia and renal tubular acidosis. A review of the literature showed that patients with SDS appeared to have an increased incidence of various transplantassociated problems. These patients frequently have underlying organ dysfunction and should … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 10 publications
0
36
0
1
Order By: Relevance
“…Tsai et al 15 reported a case of fatal congestive heart failure following a Cy-containing-conditioning regimen. Other authors have described neurological complications, 16 pulmonary complications and multiorgan failure with typical ablative regimens. 17,18 In this report, we describe our institutional experience with the use of a reduced-intensity-conditioning regimen consisting of Campath-1H, fludarabine and melphalan in seven patients with SDS, all of whom achieved excellent hematopoietic recovery and full donor chimerism with acceptable toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Tsai et al 15 reported a case of fatal congestive heart failure following a Cy-containing-conditioning regimen. Other authors have described neurological complications, 16 pulmonary complications and multiorgan failure with typical ablative regimens. 17,18 In this report, we describe our institutional experience with the use of a reduced-intensity-conditioning regimen consisting of Campath-1H, fludarabine and melphalan in seven patients with SDS, all of whom achieved excellent hematopoietic recovery and full donor chimerism with acceptable toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…There also does not appear to be a significant increase in transplant-related morbidity and mortality in SDS patients compared to other transplant populations, in contrast to previous observations. 7 Patients who received an allotransplant for marrow aplasia had a considerably better survival compared to patients transplanted for other reasons. Four of the five patients with marrow aplasia were disease free for at least 9 months after transplant in contrast to other indications where only two patients survived beyond a year.…”
Section: Discussionmentioning
confidence: 99%
“…Early attempts were associated with significant toxicity and mortality which were thought to be related to nonspecific organ dysfunction caused by the syndrome. 7 We report a patient with SDS who received an allotransplant without significant 100 day transplant-related toxicity. We also reviewed the outcomes of other patients published in the literature and noticed several trends that may provide some guidance in the timing of allotransplants in patients with SDS.…”
mentioning
confidence: 99%
“…Including this report, only 11 cases of allogeneic transplant have been reported in the literature. 3,4,[9][10][11][12][13][14] Indications for transplantation were marrow aplasia (five cases), myelodysplastic syndrome (three cases) and acute myeloid leukemia (three cases). Only five of 11 were alive at follow up, and four of them were disease-free survivors with follow-ups ranging from 9 months to 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…2 Supportive treatment with antibiotics and transfusion, and correction of malabsorption with oral pancreatic enzymes, currently allow prolonged survival without modifying the natural evolution of the disease. 1,2 Allogeneic stem cell transplantation is a valuable option when clonal disorders such as leukemic transformation, myelodysplasia or severe marrow aplasia develop 3,4 but experience in this field is very limited due to the rarity of the disease and the lack of clear-cut indications concerning the optimum timing of transplantation. We report a successful unrelated identical bone marrow transplant (BMT) in a 5-year-old boy who developed marrow aplasia after initial marrow dysplasia.…”
mentioning
confidence: 99%